Fabrication and characterization of Si/transition metal oxide solar cell - Tay, Tammy Yun Jie (Nanyang Technological University, 2020)
By 2030, Singapore aims to power 350,000 homes using solar energy [1]. As the world continues to shift its reliance of power generation from traditional sources such as burning of fossil fuel to renewable sources such as solar power, we need to continue to research and develop solar cells that exceed the performance of the present solar cell technology. Conventional method of solar cell fabrication is costly and as the search for cheaper and simpler fabrication process for solar cell continues, and there has been significant research development in using transition metal oxide (TMO) as a hole selective contact for solar cell fabrication. Due to its high work function, good selectivity and transparency, TMO is an ideal material for fabricating TMO/Si heterojunction solar cell as it can be fabricated at low temperature environment in contrast to Si solar cells. In this project, we fabricate and characterize TMO/Si heterojunction solar cell using TMOs that include vanadium oxide (V2O5) and tungsten oxide (WOx) fabricated using solution-based process. In our study, the thickness of TMO layer is varied and N2 annealing at 300°C was performed and its effects on the performance of the solar cell are investigated. The results obtained showed the performance of the solution based WOx (sWOx)/Si solar cell without N2 annealing obtained a remarkable efficiency of 9.22%.